Community planning San Jose del Llano, Miquihuana, Tamaulipas - Vargas-Tristán, Virginia (Universidad Autónoma de Tamaulipas, 2011)
Miquihuana is one of 14 Tamaulipas’s municipalities considered with a High degree of marginalization. The Sedesol in his Microrregiones’s strategy looks that localities identified since of high marginalization serve as Strategic Community Centers (CEC), for the promotion of supports, principally for the strengthening of his infrastructure and urban equipment. East CEC must be constituted in center of population attraction, which promotes a tidy growth, avoiding future problems of irregular accessions, deficit in networks of drinkable water, sewer, housing, green and recreative areas, insufficiency of urban transport, irregularities and speculation in the offer of urban soil, between others. The aim of the study was the community planeation of the locality developed San José of the Plain, by means of the application of workshops of civil participation and to generate an instrument of management that uses as base to project the socioeconomic, urban and environmental development of the locality. In the cartographic diagnosis and synthesis of the socioeconomic and environmental problematics of the locality, the most important problems were prioritized and actions appeared to solve them. Inside the principal ones they are mentioned: Supply of water, electrification, telephony, repair of approach roads, environmental pollution, zones of scattering, educational infrastructure, housing, health, paving, between others.